Math, asked by srashanthi, 7 months ago

factorize 8a³-12a²b+6ab²-b³​

Answers

Answered by bson
1

Step-by-step explanation:

8a³ = 2³a³ =(2a)³

-12a²b = 3*4a²*b= 3*(2a)²*(-b)

6ab² = 3*2a*(-b)²

-b3 = (-b)³

8a³-12a²b+6ab²-b³

= (2a)³ -3*(2a²)b+ 3* (2a)*b²-b³

=(2a-b)³

because (a-b)³=a³-3a²b+3ab²-b³

Answered by gurujeevan8
0

Answer:

pls mark me as brainliest

Step-by-step explanation:

answer is (2a+b)³

bcoz:

(a+b) ³=a³+b³+3a²b+3ab²

if we take:

(2a+b)³=(2a)³+b³+3.(2a)².b. +3.2a.b²

so, 8a³+b³+12a²b+6ab²

Similar questions